Comparison of Components and Antioxidant Activity between Selenium-enriched and Common Chlorella Extract - Di YANG; Yupeng ZHU; Qin FU; Yang ZHUANG; Kaiju MO (Shipin gongye ke-ji, 2024)
To investigate the difference of the components and antioxidant activity between the Se-enriched and the common chlorella extract, as well as the correlation between the components and antioxidant activity. This study determined the content of total nitrogen, total sugar, polyphenols, flavonoids, saponins, total selenium, polysaccharide and polysaccharide selenium in selenium-enriched and common chlorella extract and their ability to reduce Fe3+, scavenge DPPH·, ABTS+·, ·OH and O2−·, as well as the correlation between the content and antioxidant capacity. The results showed that compared with common chlorella extract, selenium-enriched chlorella extract contained more content of total sugar, polyphenol, flavonoid, total selenium, polysaccharide and polysaccharide selenium (P<0.05), but less total nitrogen and saponins (P<0.05). The Se-enriched chlorella extract had higher activity in reducing Fe3+ and scavenging DPPH· and ABTS+·, but lower activity in scavenging ·OH and O2−· than that of common chlorella extract. Correlation analysis showed that higher content of nitrogen, total sugar, polyphenols, flavonoids, saponins, total selenium, polysaccharide and polysaccharide selenium could strengthen the antioxidant activity (P<0.05). The ·OH scavenging capacity was negatively correlated with total selenium and polysaccharide selenium (P<0.05). In general, Se-enriched chlorella extract had more physiological active substances (except total nitrogen and saponins) and stronger antioxidant activity, which would provide the potential application for Se-enriched chlorella extract in health food products.